Two stereocentered HKR of anti-β,β′-diphenylpropanoxirane and anti-3-phenylethyloxiranes catalysed by Co(III)(salen)-OAc complex: enantioselective synthesis of (+)-sertraline and (+)-naproxen - Kamble, Rohit B. (New Journal of Chemistry, 2018)
The Co(III)(salen)OAc-catalyzed two stereocentered hydrolytic kinetic resolution (HKR) of anti-β,β′-diphenylmethyloxirane and anti-3-phenylethyloxiranes affords the corresponding anti-1,2-diols and oxiranes in high enantiomeric excess. The synthetic potential of this methodology is demonstrated by the enantioselective synthesis of (+)-sertraline, an antidepressant drug, and (+)-naproxen, an anti-inflammatory drug.